Analisis agroeconomico del proceso de produccion de frijol en una zona altamente tecnificada: Valle del Cauca, Colombia - Infante O, M; Pinstrup-Andersen, Per (International Center for Tropical Agriculture, 1975)
Information is provided on the most important agronomic aspects of the black bean production process in 3 municipalities in the Valle del Cauca (Ginebra, Cerrito, and Tulua), Colombia. Thirty-one bean production units of varying surface area and technology level were visited. Factors involved in the process are described: land and capital; soil availability and characteristics; agrobiological aspects of pests, diseases and weeds; availability of human, credit, and technical assistance resources; and marketing facilities. The utility of an agroeconomic methodology to help establish research strategies and priorities and government policies oriented toward increasing bean production and productivity is demonstrated. Fifty-six percent of the farmers indicated that the main problem limiting bean production is water management or availability, whereas for large farmers find insect pests such as Empoasca, Trichoplusia, chrysomelids, and Bemisia tabaci, and diseases such as angular leaf spot (Isariopsis griseola), rust (Uromyces phaseoli), bacterial blight (Xanthomonas phaseoli), root rots, and viruses to be major problems. Yields ranged between 0-2000 kg/ha and a gross margin variation between - $3767 and $25,000/ha was noted. (CIAT)